Video‐rate tunable colour electronic paper with human resolution - Ade Satria Saloka Santosa; Yu-Wei Chang; Andreas B. Dahlin; Lars Österlund; Giovanni Volpe; Kunli Xiong (Nature, 2025)
Abstract As demand for immersive experiences grows, displays with smaller sizes and higher resolutions are being viewed increasingly closer to the human eye 1 . As the size of emitting pixels shrinks, the intensity and uniformity of their emission are degraded while colour cross-talk and fabrication complexity increase, making ultra-high-resolution imaging challenging 2–4 . By contrast, electronic paper, which uses ambient light for visibility, can maintain high optical contrast regardless of pixel size, but cannot achieve high resolution 5,6 . Here we demonstrate electronic paper with electrically tunable metapixels down to ~560 nm in size (>25,000 pixels per inch) consisting of WO 3 nanodisks, which undergo a reversible insulator-to-metal transition on electrochemical reduction. This transition enables dynamic modulation of the refractive index and optical absorption, allowing precise control over reflectance and contrast at the nanoscale. By using this effect, the metapixels can achieve pixel densities approaching the visual resolution limit when the display size matches the pupil diameter, which we refer to as retina electronic paper. Our technology also demonstrates full-colour video capability (>25 Hz), high reflectance (~80%), strong optical contrast (~50%), low energy consumption (~0.5–1.7 mW cm – 2 ) and support for anaglyph 3D display, highlighting its potential as a next-generation solution for immersive virtual reality systems.